AWAKE readiness for the study of the seeded self-modulation of a 400 GeV proton bunch. (29th November 2017) - Muggli, P; Adli, E; Apsimon, R; Asmus, F; Baartman, R; Bachmann, A-M; Barros Marin, M; Batsch, F; Bauche, J; Berglyd Olsen, V K; Bernardini, M; Biskup, B; et al.
Abstract: AWAKE is a proton-driven plasma wakefield acceleration experiment. We show that the experimental setup briefly described here is ready for systematic study of the seeded self-modulation of the 400 GeV proton bunch in the 10 m long rubidium plasma with density adjustable from 1 to 10 × 10 14 cm −3 . We show that the short laser pulse used for ionization of the rubidium vapor propagates all the way along the column, suggesting full ionization of the vapor. We show that ionization occurs along the proton bunch, at the laser time and that the plasma that follows affects the proton bunch.